1997
DOI: 10.1007/pl00004966
|View full text |Cite
|
Sign up to set email alerts
|

Is α1D-adrenoreptor protein detactable in rat tissues?

Abstract: We have used the alpha1D-adrenoceptor selective antagonist, BMY 7378, the alpha1D-selective agonists, adrenaline and phenylephrine, the alpha1A-selective antagonists, (+)-niguldipine, SB 216469 and WB4101, and the non-subtype-selective alpha1-adrenoceptor antagonist, nemonapride, to investigate the presence of alpha1D-adrenoceptors in rat tissues at the protein level. Radioligand binding studies using [3H]prazosin as the radioligand were performed in three tissues containing alpha1D-adrenoceptor mRNA, spleen, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(51 citation statements)
references
References 31 publications
(61 reference statements)
2
49
0
Order By: Relevance
“…4A), and 5-methylurapidil. The proportions of high-and low-affinity sites were almost equal ( (Oshita et al, 1993;Yang et al, 1997) and in Krebs' incubation buffer, which was essentially identical with that used for intact tissue segment binding procedure. In both cases, […”
Section: Resultsmentioning
confidence: 77%
“…4A), and 5-methylurapidil. The proportions of high-and low-affinity sites were almost equal ( (Oshita et al, 1993;Yang et al, 1997) and in Krebs' incubation buffer, which was essentially identical with that used for intact tissue segment binding procedure. In both cases, […”
Section: Resultsmentioning
confidence: 77%
“…However, in contrast with the aorta but like the tail artery, the endogenous noradrenaline level in the spleen was high and was markedly reduced by reserpine treatment. Present and previous functional or binding studies have clearly demonstrated the exclusive presence of alpha-1B AR subtype in rat spleen, irrespective of reserpine treatment (Kenakin & Novak, 1988;Yang et al, 1997;Buckner et al, 2002;Zhang et al, 2002). Thus, it does not appear that noradrenaline depletion and/or lack of adrenergic input necessarily cause the changes of alpha-1 AR expression and supersensitivity in sympathetically innervated tissues all.…”
Section: N Taki Et Al Alpha-1d Adrenoceptors In Supersensitivity 653mentioning
confidence: 66%
“…It has been reported that methoxamine is a relatively selective a 1A-adrenoceptor agonist (9), and Minneman et al (10) reported that methoxamine is approximately 20-fold more potent to activate a1a-than a1b-and a1d-adrenoceptors in mediating [ 3 H]inositol phosphate formation. It was suggested that a1A-adrenoceptors might not be so abundant in the rat mesenteric artery (10,11). On the other hand, noradrenaline and phenylephrine show relative selectivity for the a 1d-adrenoceptor subtype (10, 11).…”
Section: Discussionmentioning
confidence: 99%